ChemInform Abstract: Exploring the Aldol Reaction in the Synthesis of Bioactive Compounds. Issue 17 (April 2016) - Ferreira, Marco A. B.; Dias, Luiz C.; Leonarczyk, Ives A.; Polo, Ellen C.; de Lucca, Emilio C.
Abstract: Review: 143 refs.